Residents’ perception and environmental assessment of a waste recycling centre: a case study of Buenos Aires City (Argentina) - Giustiniani, Emilia (2023)
Urban waste management should ensure minimal environmental impact and local context adaptation. We present an assessment of the municipal Recycling Centre in Buenos Aires City (Centre), which processes recyclable materials, food waste, municipal tree pruning, and construction and demolition waste. To evaluate the Centre´s socio-environmental performance, we conducted a study in an area of ~ 9 km2 around the Centre. First, we surveyed nearby residents to gather their perceptions of the Centre and neighbourhood cleanliness. Second, we analysed indicators of air quality by dust traps, street cleanliness by applying an index evaluating street littering and provision of municipal waste containers, and vehicular and pedestrian traffic at the entrance of the Centre. About 80% of local residents had a negative perception of street cleanliness, largely due to litter scattered by neighbours around waste containers and pavements. Among residents aware of the Centre´s existence, 60% reported negative perceptions, linked with dust emissions and heavy truck traffic. Positive perceptions were linked to the awareness about the Centre´s role in waste recycling and employment. Air quality revealed the highest levels of dust particles near the Centre and on avenues, irrespective of their distance from the Centre. The cleanliness index was lowest in the Centre´s immediate vicinity. Intense truck traffic was documented at the Centre´s entrance, also reported as a negative issue in the surveys. These findings highlight negative environmental impacts on the well-being of residents in the Centre´s surroundings, some of them associated with the Centre’s operations. The study identifies opportunities for significant improvement to address these issues.